(untitled) (Comprehensive Journal of Science, 2025)
Startups and small businesses play an important role in developing local economies and enhancing competitiveness in markets. With the increasing reliance on innovation and entrepreneurship, small and emerging businesses have become the backbone of many economies, contributing to the creation of new jobs, increased productivity, and the promotion of innovation. In recent years, local markets around the world have shown growing interest in supporting startups and small businesses due to their pivotal role in economic and social development, especially in developing countries. Globalization and increasing global competition have led to significant transformations in local markets, where large companies alone can no longer monopolize the market. Startups and small businesses have started competing with large companies by offering innovative products and services that meet specific consumer needs more quickly and flexibly. In many countries, start-ups and small businesses make up a significant portion of the total number of companies, and they are responsible for a large share of employment and productivity. According to recent economic reports, small businesses account for about 90% of all companies worldwide and contribute up to 50% of the GDP in some developing countries. These figures highlight the importance of these enterprises in promoting economic stability and sustainable growth. Competitiveness is a key element in modern economies. Start-ups and small businesses provide market dynamism by offering innovative solutions and responding quickly to changes in consumer needs, making them play a crucial role in enhancing competitiveness. By leveraging digital technology and adopting innovative marketing strategies, these businesses can successfully compete in local markets and even open new markets at both the local and international levels. Despite the significant potential offered by these projects, they face numerous challenges that may hinder their ability to grow and compete. Among the main challenges are lack of funding, weak infrastructure, complex bureaucratic procedures, and difficulty accessing markets. In addition, many startups lack the managerial expertise and resources necessary to grow their businesses. Startups and small enterprises are the backbone of both developing and developed economies, as they contribute to creating a dynamic environment that fosters innovation and competitiveness. With the rapid changes in global markets, these projects have become an integral part of economic growth strategies. In this context, the importance of the current study lies in highlighting the growing role of startups and small enterprises in enhancing competitiveness in local markets, analyzing the factors that affect their success, and providing recommendations to support these projects in the future. In addition, this research aims to explore how start-ups and small enterprises affect competitiveness in local markets by studying the factors that contribute to their success and the challenges they face. These enterprises play an important role in stimulating competitiveness in local markets by offering innovative products and services and responding quickly to changes in consumer needs.